2016
DOI: 10.1149/2.0511614jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Cations on Hydrogen Oxidation Reaction of Carbon Supported Platinum

Abstract: Effect of organic cations on hydrogen oxidation reaction (HOR) of carbon supported platinum (Pt/C) is investigated using three 0.1 M alkaline electrolytes, tetramethylammonium hydroxide (TMAOH), tetrabutylammonium hydroxide (TBAOH) and tetrabutylphosphonium hydroxide (TBPOH). Rotating disk electrode experiments indicate that the HOR of Pt/C is adversely impacted by time-dependent and potential-driven chemisorption of organic cations. In-situ infrared reflection adsorption spectroscopy experiments indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…0.1 V vs. RHE was observed by several researchers. 72,[95][96][97][98][99] Surface infrared and neutron reflectometry studies indicated that the chemisorbed layer contains highly concentrated ammonium hydroxide and does not allow fast hydrogen and water transport. 72,100 This means the water distribution in the AEMFC anode is nonuniform and the AEMFC anode requires high porosity for fast water transport, yet is more prone to flooding.…”
Section: Current Status Of Aemfc Durabilitymentioning
confidence: 99%
“…0.1 V vs. RHE was observed by several researchers. 72,[95][96][97][98][99] Surface infrared and neutron reflectometry studies indicated that the chemisorbed layer contains highly concentrated ammonium hydroxide and does not allow fast hydrogen and water transport. 72,100 This means the water distribution in the AEMFC anode is nonuniform and the AEMFC anode requires high porosity for fast water transport, yet is more prone to flooding.…”
Section: Current Status Of Aemfc Durabilitymentioning
confidence: 99%
“…While the complexity of this task is daunting, literature already provides many examples where manipulating solution structure enhances electrocatalytic rates. In alkaline HER/HOR, cation effects provide a simple demonstration of this approach 7,24,25 . More nuanced effects can be realized with ionic liquid electrolytes in the carbon dioxide reduction reaction (CO2RR) and oxygen reduction reaction (ORR) [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…The coadsorption may block some of the active sites of catalyst and increase the barrier for hydrogen access. [ 162–165 ] The group of Kim observed that phenyl groups often present in polyaromatic AEI reduce the HOR activity leading to inferior AEMFC performance. As is shown in Figure a, Pt/C catalyst in phenyl containing benzyltrimethylammonium hydroxide (BTMAOH) organic solution exhibited a clear drop of HOR current density during 0.0 to 0.06 V, compared with phenyl free tetramethylammonium hydroxide (TMAOH) solution.…”
Section: Anion Exchange Ionomermentioning
confidence: 99%
“…The coadsorption may block some of the active sites of catalyst and increase the barrier for hydrogen access. [162][163][164][165] The group of Kim observed that phenyl groups often present [166] Copyright 2018, American Chemical Society. b) Relationship of AEMFC performances of different AEI structures and their phenyl adsorption energies; DFT-optimized geometries of various aromatic compounds and calculated adsorption energies.…”
Section: Interactions With Catalystmentioning
confidence: 99%